Xilotecnia of the wood of Acacia schaffneri from the state of hidalgo, Mexico - Machuca-Velasco, Roberto; Borja de la Rosa, Amparo; Corona-Ambriz, Alejandro; Zaragoza-Hernández, Idalia; Arreola-Avila, Jesús Guadalupe; Jiménez-Machorro, Javier (Maderas. Ciencia y Tecnología, 2017)
The genus Acacia spp belongs to the family Leguminosae, with more than 1300 species distributed naturally in all continents except Europe. In Mexico there are 85 species, of which 46 are endemic, most located in arid and semiarid regions, being Acacia coulteri and Acacia farnesiana the most widely distributed. The aim of this study was to determine the technological characteristics of the wood of Acacia schaffneri. To determine the anatomical characteristics, the methodology of Autonomous Chapingo University’s wood anatomy laboratory was used; for the physical properties, standards NOM EE-117-1981 and NMX-EE-167-1983 were used, and in calculating the mechanical properties the mathematical formulas were employed. The wood is reddish brown and has interlocked grain with diffuse porosity, aliform confluent parenchyma and in confluent bands, and crystals and gums. The proportion of cells was 11,87% vessel elements, 50,65% fibers 27,76% axial parenchyma and 9,81% ray parenchyma. Basic density was 880 kg/m3, tangential, radial, axial and volumetric shrinkage values were 10,57%; 4,97%; 0,10% and 15,82 % respectively, and fiber saturation point was 19,97%. The mechanical properties were very high, so it can be used in the manufacture of floors and in building constructions.